2010
DOI: 10.1016/j.virol.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Alternate receptor usage of neuropilin-1 and glucose transporter protein 1 by the human T cell leukemia virus type 1

Abstract: Recent studies have demonstrated that neuropilin 1 (NP-1) is involved in HTLV-1 entry; however, the role NP-1 plays in this process is not understood. We demonstrated that ectopic expression of human NP-1 but not NP-2 cDNA increased susceptibility to HTLV-1. SiRNA-mediated inhibition of NP-1 expression correlated with significant reduction of HTLV-1 Env-mediated fusion. The vascular endothelial growth factor (VEGF165) caused downmodulation of surface NP-1 and inhibited HTLV-1 infection of U87 cells. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…This hypothesis was confirmed in a recent study [3]. NRP-1 is a 130 kDa single membrane spanning glycoprotein which acts as the co-receptor for Semaphorin 3a and VEGFA 165 .…”
Section: Not One But Three Receptor Molecules: Glut1 Hspg and Nrp-1supporting
confidence: 66%
“…This hypothesis was confirmed in a recent study [3]. NRP-1 is a 130 kDa single membrane spanning glycoprotein which acts as the co-receptor for Semaphorin 3a and VEGFA 165 .…”
Section: Not One But Three Receptor Molecules: Glut1 Hspg and Nrp-1supporting
confidence: 66%
“…A previous study has shown that the in vitro infection of human astrocytes with HTLV-1 results in the release of proinflammatory cytokines (9). Furthermore, it has been found that neuropilin-1 and glucose transporter protein 1 are involved in HTLV-1 infection of U87 astroglioma cells and human primary astrocytes (10). Overall, these available data suggest that HTLV-1-infected astrocytes might be involved in the progression of HAM/TSP.…”
mentioning
confidence: 74%
“…Such cooperation was also recently functionally demonstrated by data showing that inhibition of HTLV-1 entry into primary astrocytes required the blocking of the interactions with both NRP-1 and GLUT1 [14]. …”
Section: The Host Cell Actors: the Htlv-1 Receptorsmentioning
confidence: 80%